PEPA.AI - Generating Insights for Informing Agrifood Systems Policy Decisions - Mockshell, Jonathan; Garcia Gallego, Jeffrey Steven; Mosquera Escobar, Leslie Estefany; Blanco Garcia, Maria Alejandra; Nielsen Ritter, Thea; Franco Betancourt, Gabriel; Mwanzia, Leroy; Garcia, Carolina; Resnick, Danielle (2025)
The PEPA Microsimulation Tool is an initiative led by the Alliance of Bioversity International and CIAT under Policy innovation CGIAR program developed by Foresight and Applied Economics for Impact (FAE) and Data Management & Open Science (DMOS) teams within the PISA4Impact program. This innovative tool leverages artificial intelligence to empower stakeholders in Political Economy and Policy Analysis (PEPA), providing a structured, user-friendly approach to analyze policy issues and support evidence-based decision-making.